The applicability of constructivist user studies: how can constructivist inquiry inform service providers and systems designers? Constructivist inquiry, Case study, Systems design, User behaviour - Alison Pickard; Pat Dixon (Information Research: An International Electronic Journal)
This paper has attempted to clarify the ways in which individual, holistic case studies, produced via the process of constructivist inquiry, can be tested for trustworthiness and applied to other, similar situations. Service providers and systems designers need contextual information concerning their users in order to design and provide systems and services that will function effectively and efficiently within those contexts. Abstract models can only provide abstract insight into human behaviour and this is rarely sufficient detail upon which to base the planning and delivery of a service. The methodological issues which surround the applicability of individual, holistic case studies are discussed, explaining the concept of 'contextual applicability.' The relevance and usefulness of in-depth case study research to systems designers and service providers is highlighted.